2021
DOI: 10.18865/ed.31.s1.301
|View full text |Cite
|
Sign up to set email alerts
|

Looking Back to Leap Forward: A Framework for Operationalizing the Structural Racism Construct in Minority and Immigrant Health Research

Abstract: Racism is now widely recognized as a fundamental cause of health inequali­ties in the United States. As such, health scholars have rightly turned their attention toward examining the role of struc­tural racism in fostering morbidity and mortality. However, to date, much of the empirical structural racism-health dispari­ties literature limits the operationalization of structural racism to a single domain or orients the construct around a White/ Black racial frame. This operationaliza­tion approach is incomprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…There are increasing calls for research that centers immigrant health care experiences and health outcomes as products of structural racism and resulting social inequalities ( Dennis et al, 2021 ). This study shows how multi-level forms of racism and subsequent inequities shaped foreign-born Latinx women's health care interactions and experiences during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are increasing calls for research that centers immigrant health care experiences and health outcomes as products of structural racism and resulting social inequalities ( Dennis et al, 2021 ). This study shows how multi-level forms of racism and subsequent inequities shaped foreign-born Latinx women's health care interactions and experiences during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While it is asserted that immigrants enter the U.S. with better health compared to U.S. natives, research has shown that their health often deteriorates the longer they reside in the U.S. ( Acevedo-Garcia & Bates, 2008 ; Castañeda et al, 2015 ; Crimmins et al, 2007 ; Franzini et al, 2001 ) . Such a decline in immigrant health outcomes has been attributed to several multilevel factors, including health systems, interpersonal dynamics, access to resources, and individual behaviors, but xenophobia, or exclusion and discrimination of others based on national origin, which includes structural racism as well as perceived discrimination is often overlooked in the U.S. immigrant experience ( Dennis et al, 2021 ; Samari et al, 2021 ; Viruell-Fuentes et al, 2012 ). Racism has long been linked to greater health disparities ( Gee & Ford, 2011 ; Williams et al, 1997 ), only to be exacerbated by COVID-19 ( Zalla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Institutional racism, within organizations in the United States, involves policies, practices, and procedures which privilege majority White racial groups (Carmichael & Hamilton, 1967 ; Dennis et al, 2021 ; Gee & Hicken, 2021 ). Thus, institutional racism is defined as the existence of systematic policies, laws, and practices that provide differential access to goods, services, and opportunities because of socially constructed racial identity.…”
Section: Introductionmentioning
confidence: 99%
“…As a settler-colonial state which achieved global financial power through slave labor and imperialism, the structures which continue to support the political, financial, judiciary, and educational systems maintain a hierarchical status quo based on established racial groups. 19 Racism may be globally pervasive, but the structure of the system and the experience of living within it is different in the U.S. than it is in Mexico, Brazil, South Africa, India, or any other country.…”
Section: Discussionmentioning
confidence: 99%